Strengthening the efficiency of cold chain management in halal food industry by identifying the crucial barriers - Iskandar,, Muhammad Affifuddin; Mahamad Maifiah, Mohd Hafidz; Ahmad, Anis Najiha (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia (IIUM), 2021)
The global demand for halal food is due to its desired characteristics of quality, cleanliness and safety. The management of the cold chain is to ensure the freshness and consistency of the food during processing and distribution. Nevertheless, many barriers are affecting the efficiency of cold chain management. The objective of this research was to identify the key barriers contributing to the inefficiency of cold chain management, in particular in the segment of the halal food industry.